Do Generation Y Consumers Differ in their Mobile Banking Utility? Evidence from South Africa: Array - Van Deventer, Marko (Acta Universitatis Danubius. Œconomica, 2021)
Mobile banking utility such as convenience, usefulness and ease of use as well the time and money saving properties associated with using mobile banking, is important to banking consumers. As such, it is important that retail banks invest the necessary time and resources into their mobile banking channels, not only to ensure adequate mobile banking utility, but also to differentiate its mobile channels from other mobile banking channels in the highly competitive mobile banking market. To this end, the purpose of this study was to investigate mobile banking utility differences amongst Generation Y consumers of the major South African retail banks. A descriptive and single cross-sectional research design informed the methodology followed in this study. Self-administered survey questionnaires were used to collect data from a convenience sample of 334 Generation Y mobile banking consumers. Descriptive statistics, reliability and validity measures, Pearson’s product-moment correlation analysis, collinearity diagnostics as well as one-way analysis of variance (ANOVA) were used to analyse the data. The results suggest that there are differences between Generation Y consumers of the major South African retail banks and attitudes towards mobile banking, perceived usefulness, ease of use, compatibility and perceived mobile banking self-efficacy. Retail banks can use the findings of this study to improve its mobile banking utility and in doing so, gain greater market share and improved customer satisfaction and loyalty.